Pengaruh E-Satisfaciong Terhadap E-Loyalty Dengan Menggunakan Moderator E-Trust Pada Situs Kaskus.Com Di Surabaya - Sanjaya, Ricky Immanuel (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Online retailers should be able to increase customer satisfaction (e-satisfacton) so that it could be created an e-loyalty is high. Satisfaction of online services is identified from the alignment of expectations of consumers with the realization of the service consumer. While e-loyalty, frequency of recurring purchases are identified by consumers online. To build e-loyalty, also turned out to be moderated by customer trust (trust) for the online services provided. To that end, the study will provide an in-depth study about influence of e-satisfaction against e-loyalty with moderators on the e-trust FJB Kaskus. In this research is the research on experimental studies or conclusive causal research. Sampling techniques used are non probability sampling. This type of method used is purposive sampling. The sample used was 100 FJB Kaskus consumer. Data collected by using a questionnaire. Analysis technique that is used is a simple linear regression analysis and linear regression analysis with moderators. The results of this analysis demonstrates that e-satisfaction affect e-loyalty, FJB Kaskus consumer. In addition found also that it turns to e-trust consumer FJB Kaskus cannot act as a moderator for the relationship between satisfaction with the purchase of e-e-loyalty.